2014
DOI: 10.1038/nsmb.2769
|View full text |Cite
|
Sign up to set email alerts
|

More-powerful virus inhibitors from structure-based analysis of HEV71 capsid-binding molecules

Abstract: Enterovirus 71 (HEV71) epidemics amongst children and infants result mainly in mild symptoms, however, especially in the Asia-Pacific region, infection can be fatal. At present no therapies are available. We have used structural analysis of the complete virus to guide the design of HEV71 inhibitors. Analysis of complexes with four 3-(-4-pyridyl)-2-imidazolidinone derivatives with varying anti-HEV71 activities, pinpointed key structure-activity correlates. We then identified additional potentially beneficial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
100
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 48 publications
4
100
0
1
Order By: Relevance
“…Knowledge of the precise interactions between the viral capsid and capsid binding compounds may help to develop novel and yet more potent antivirals. A novel class of EV71 capsid binders was recently reported which were designed based on the crystal structure of the EV71 capsid (27). In that particular study, cocrystals of the EV71 capsid with the compounds revealed an interaction with Asp112 and/or Ile113, underlining the importance of these interactions and corroborating the findings of our modeling study.…”
supporting
confidence: 74%
“…Knowledge of the precise interactions between the viral capsid and capsid binding compounds may help to develop novel and yet more potent antivirals. A novel class of EV71 capsid binders was recently reported which were designed based on the crystal structure of the EV71 capsid (27). In that particular study, cocrystals of the EV71 capsid with the compounds revealed an interaction with Asp112 and/or Ile113, underlining the importance of these interactions and corroborating the findings of our modeling study.…”
supporting
confidence: 74%
“…The range of HBV capsid protein structures, liganded and apo, icosahedral and nonicosahedral, led us to suggest that in solution Cp can be found in a diverse ensemble of quaternary structures that can be biased by CpAM binding, mutations, and crystal contacts. An analogous observation was made with experimental antiviral ligands that bind to picornavirus capsids, which make small tertiary structure changes to the capsid and stabilize capsids to inhibit nucleic acid release; these ligands appear to act by modifying picornavirus capsid dynamics, entropically stabilizing them (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…pro (6,20,21), and pleconaril, GPP3, and cyclosporine block the entry of enteroviruses and coxsackieviruses (22)(23)(24). However, none of these reported inhibitors have been able to be advanced to clinical therapeutics.…”
mentioning
confidence: 99%